2017
DOI: 10.1038/pr.2017.8
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of C5b9 immunostaining in the diagnosis of neonatal hemochromatosis

Abstract: Diagnosis and therapeutic management of GALD cannot only be based on C5b9 expression in liver samples as it is not specific of this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 75 publications
0
11
0
1
Order By: Relevance
“…Nonimmune complex-mediated complement activation may occur in this setting. Seventy-five percent staining for C5b-9 as a cutoff point for GALD was challenged by Dubruc et al 18 About a quarter of their non-GALD cases (n ¼ 36) had more than 75% positive parenchymal staining; on the other hand, only a quarter of GALD cases (n ¼ 25) showed more than 75% parenchymal staining. In the same study, 3 cases of liver disease without EHNRS also showed more than 75% parenchymal C5b-9 staining.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonimmune complex-mediated complement activation may occur in this setting. Seventy-five percent staining for C5b-9 as a cutoff point for GALD was challenged by Dubruc et al 18 About a quarter of their non-GALD cases (n ¼ 36) had more than 75% positive parenchymal staining; on the other hand, only a quarter of GALD cases (n ¼ 25) showed more than 75% parenchymal staining. In the same study, 3 cases of liver disease without EHNRS also showed more than 75% parenchymal C5b-9 staining.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have focused on the utility of C5b-9 immunohistochemistry in the diagnosis of NH. 18 However, some centers, including tertiary academic hospitals, do not have standardized C5b-9 immunohistochemistry for clinical use. The need for this antibody often arises from the observation of hepatic and extrahepatic siderosis of hemochromatotic type, that is, the NH phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 44 cases with neonatal liver failure (22 NHs, and 22 non-NHs) that were found only six in the NH group were definite GALD if based on C5b-9 IHC ( 20 ). Dubruc et al reported C5b-9 that was expressed in 100% of GALD cases, yet also in 27% of non-GALD cases (enterovirus hepatitis, bile acid synthetic defect, DGUOK mutation, Gaucher disease, cystic fibrosis, and giant-cell hepatitis with autoimmune hemolytic anemia) ( 30 ). Regarding these controversial findings, a careful application and interpretation of the C5b-9 IHC are indispensable for an accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Son positivos a la tinción inmunohistoquímica C5b-9; esto no es específico de GALD; sin embargo, se ha demostrado asociación cuando se observa en más del 75% de la muestra. 19,20 Los canalículos biliares se describen con tapones biliares y los conductos portales relativamente intactos o, bien, con pocos datos de inflamación. El proceso de inflamación puede verse como infiltración de macrófagos y neutrófilos.…”
Section: Diagnósticounclassified